Developing technology teachers'creative teaching skills through the integration of educational technologies in honours programme in a South African university - Nkosi, Praygod Bonginkosi (My University, 2025)
The advancement of technology continues to significantly influence classroom practices, modifying the ways in which teaching, and learning occur. However, many teachers are often left behind in this transformation, resulting in feelings of demotivation, frustration, and a sense of being outdated particularly in issues relating to the integration of Educational Technologies. To bridge this gap, it is imperative for the Ministry of Education to ensure that teachers are up to date with emerging technological developments that have the potential to enhance classroom teaching and learning. Achieving this requires the implementation of continuous professional development initiatives, such as targeted training programmes, workshops, and seminars, to equip teaches with the necessary knowledge and skills to effectively integrate technology into their classroom practices. Therefore, teachers must inevitably rise to the challenges by gaining the knowledge necessary to use Educational Technologies in the classroom effectively. Moreover, the importance of making the education and training systems receptive to the demands of the new skills needed to navigate a more technologically driven world cannot be stressed enough. This study aimed to explore the development of Technology teachers’ Creative Teaching Skills by integrating Educational Technologies in a Senior Phase classroom. The enquiry was conducted among a sample of Honours students in a South African University, with most students practising as Technology teachers. Qualitative methods were engaged to obtain data from group interviews before and after the intervention programme, semi-structured interviews, document analysis, and non-participant observation. Data were analysed using qualitative content analysis to understand how teachers develop their Creative Teaching Skills through integrating Educational Technologies. The findings were multi-fold. First, teachers do not regularly use Educational Technologies as expected in the digital age, possibly due to various influencing factors. Second, there is a lack of knowledge and skills among teachers regarding the integration of Educational Technologies into their teaching. Third, Creative Teaching Skills can be enhanced through targeted professional development vi programmes. Fourth, inadequate ICT infrastructure and limited resources in schools hinder effective integration of Educational Technologies. Finally, the absence of clear policies on ICT infrastructure and resources further restricts teachers from fully leveraging Educational Technologies. These significant findings suggest that teachers developed Creative Teaching Skills, gained experience, and transformed classroom practice. Teachers’ viewpoints on integrating Educational Technologies were fortified with knowledge and facts as they gained insights while participating in the intervention programme.
Thesis (Ph.D. (Technology Education)) -- University of Limpopo, 2025
Keywords: Educational Technologies; Creative Teaching; Integration; Creative lesson; Educational technology; Technology; Creative teaching; Education, Higher -- South Africa; Teaching -- Aids and devices